2021
DOI: 10.1371/journal.ppat.1009517
|View full text |Cite
|
Sign up to set email alerts
|

Host factor Rab11a is critical for efficient assembly of influenza A virus genomic segments

Abstract: It is well documented that influenza A viruses selectively package 8 distinct viral ribonucleoprotein complexes (vRNPs) into each virion; however, the role of host factors in genome assembly is not completely understood. To evaluate the significance of cellular factors in genome assembly, we generated a reporter virus carrying a tetracysteine tag in the NP gene (NP-Tc virus) and assessed the dynamics of vRNP localization with cellular components by fluorescence microscopy. At early time points, vRNP complexes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…To further corroborate the role of Rab11a in the transport of vRNPs across TNTs, we used Rab11a knockout [KO]A549 cells generated by CRISPR/Cas9 [ 12 ] and wild type [WT]A549 cells as a control. As before, cells were infected with either NL09 or P99 viruses and then stained for NP, Rab11a and F-Actin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further corroborate the role of Rab11a in the transport of vRNPs across TNTs, we used Rab11a knockout [KO]A549 cells generated by CRISPR/Cas9 [ 12 ] and wild type [WT]A549 cells as a control. As before, cells were infected with either NL09 or P99 viruses and then stained for NP, Rab11a and F-Actin.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are needed to determine whether the same transport mechanism is active within TNTs and, conversely, whether Rab11a-actin dynamics may function in vRNP transport both within and between cells. Although Rab11a has been shown to be important for trafficking and efficient assembly of IAV genomes [ 2 , 8 , 12 ], we have shown that the loss of Rab11a does not completely abrogate genome assembly and viral particle release, indicating that there may exist an alternative pathway for canonical assembly of virions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, an alternative model has been proposed in which Rab11a and vRNPs are recruited to membranes of remodeled endoplasmic reticulum (ER), leading to the biogenesis of irregularly coated vesicles (ICVs), which ensure transport of vRNPs from the ER to the plasma membrane ( 22 ). Rab11a has also been implicated in the formation of liquid organelles promoting genome assembly and mediating cell-cell spread and reassortment of IAV genomes via tunneling nanotubes ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%